Pengaruh Komitmen Organisasi terhadap Kinerja Karyawan PT. Pelindo (Persero) Samarinda melalui Lingkungan Kerja sebagai Mediator - Dyah Ayu Puspita; Vera Anitra; Rinda Sandayani Karhab (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the effect of organizational commitment on employee performance with the work environment as a mediating variable at PT Pelindo (Persero) Samarinda Branch. The main issue addressed is whether organizational commitment has a direct effect on employee performance and to what extent the work environment mediates this relationship. The scope of the study includes all 62 employees at PT Pelindo (Persero) Samarinda Branch. A quantitative approach was employed using a survey method, with data collected through a Likert-scale questionnaire. Data analysis was conducted using structural equation modeling with the PLS-SEM (Partial Least Squares-Structural Equation Modeling) approach, supported by SmartPLS 3 software. Total sampling was applied due to the relatively small population. The findings indicate that organizational commitment does not have a significant direct impact on employee performance, but has a significant positive effect on the work environment. The work environment, in turn, has a significant positive effect on employee performance and serves as a full mediator in the relationship between organizational commitment and performance. The study concludes that while organizational commitment alone does not directly enhance performance, its role in fostering a supportive work environment is crucial. Therefore, it is recommended that the company prioritize creating a positive and supportive work environment to promote optimal employee productivity.